Pengaruh Hukum Adat Terhadap Ketentuan Waris Pasal 183, 185, dan 209 Kompilasi Hukum Islam Perspektif Teori Receptio a Contrario - Kasumawati, Devi (FASYA Press, 2021)
The presence of Kompilasi Hukum Islam (KHI) which in the beginning was anticipated as a source of Islamic civil law after releasing in Indonesia having such a pro and contra. That’s because there are some provisions that don’t fit with the classical fiqh books. Though it is said that KHI in the formulation is based on a study of the books of fiqh, especially Shafi’i. According to several parties, like Habiburrahman in his research, there are elements of customary law comes in, especially in the chapters concerning about inheritance. Based on the statement that KHI was influenced by customary law, this research aims (1) to study KHI subsection 183 about the division of inheritance peacefully, subsection 185 about representation of heirs, and subsection 209 about obligatory bequests for adopted children; (2) how is the influence of customary law against those three articles of KHI on perspective of Receptio a Contrario Theory. This research was classified into normative research. Used data is secondary data. The process of gathering data using documentation methode according to the conceptual approach. Data was analyzed by descriptive qualitative methode. As for verifying the validity of the data using triangulation techniques. The result of research showing that subsection of 183 about division of inheritance peacefully has something in common with the tradition of Indonesian society that share their inheritance deliberately. While subsection 185 about representation of heirs was reflected family system which adopted by the majority of Indonesian society, with the name bilateral system. It can be seen from the possibly of replacement the heirs for orphaned grandchildren from deceased mother, which is not accommodated in the classical Islamic inheritance system. Subsection 209 about obligatory bequests for adopted children is an alternative solution for adopted children who didn’t get a share when his/her adoptive parents died. This policy is enforced due to the practice of adoption is something usual in Indonesia. According to the Receptio a Contrario theory, the customary law can be accepted if only it’s not contradictory with Islamic law. Based on the study which researchers did, although all three subsection are influenced by customary law, but the values that contained in there already accordance with the Islamic law.